Dietary vitamin D affects cell-mediated hypersensitivity but not resistance to experimental pulmonary tuberculosis in guinea pigs. - Hernandez-Frontera, E (1993)
Outbred, Hartley strain guinea pigs were fed purified diets varying only in their levels of vitamin D. The amounts of vitamin D in the diets were adjusted to represent 0, 25, 50, 100, or 200% of the recommended level (1,180 IU/kg of body weight) for guinea pigs. In some experiments, half of the animals in each diet group were vaccinated with Mycobacterium bovis BCG vaccine at the time the diets were introduced. Six weeks later, all guinea pigs were infected by the respiratory route with a low dose of virulent M. tuberculosis H37Rv. Vitamin D-deficient animals exhibited marked reductions in levels of the major vitamin D metabolite, 25-hydroxyvitamin D3, in plasma. Altered vitamin D intake was accompanied by changes in antigen (purified protein derivative)-induced, cell-mediated immune responses both in vivo (tuberculin hypersensitivity) and in vitro (lymphoproliferation). Dermal tuberculin reactivity developed more slowly in vitamin D-deficient guinea pigs but eventually achieved normal levels. The proliferation of splenocytes cultured with purified protein derivative was suppressed by both deficiency and excess of dietary vitamin D. Vitamin D status did not affect the abilities of naive guinea pigs to control primary, pulmonary tuberculosis, nor did it influence the protective efficacy of BCG vaccination. We conclude that changes in dietary vitamin D are associated with alterations in some cellular immune functions but may not be an important determinant of disease outcome in pulmonary tuberculosis, as has been suggested previously.